Fast Food Consumption Behavior in Adolescents - Audia Lestari; Afiah Fakhira; Alfiah Ismiana; Annisaa Annisaa (Muhammadiyah International Public Health and Medicine Proceeding, 2021)
The nutritional needs of adolescents need to be considered because during adolescence there is rapid growth and development. Unhealthy eating habits will affect the nutritional intake of adolescents. Unhealthy foods such as fast food are consumed by teenagers. At a time when everything is as modern as it is now, teenagers want everything fast-paced, including choosing food fast food is also kn own to the public as junk food. Junk food is defined as junk food or food that has no nutrition for the body. Eating junk food is not only useless but can also be detrimental to health. Fast food comes from western countries which generally have high fat and calorie content. Descriptive research method with a qualitative approach to the method of phenomenology. The sample in this study was four (4) students consisting of one grade 1 high school, two grade 2 high school students, and 1 grade 3 senior high school student. This study wants to explore the phenomena experienced by students in consuming fast food. Many factors influence teenagers to consume fast food. These factors are discussed based on research articles and book references. Factors that influence the consumption of fast food include taste, price, comfortable place, and the influence of peers. Fast food can increase the risk of several diseases, such as obesity, diabetes, hypertension, and blood lipid disorders or dyslipidemia. Obesity or overweight is experienced by many children, adolescents, and adults. Obesity occurs due to changing lifestyles, including eating patterns that often eat fast food. Eating fast food too often does not only lead to obesity. However, obesity experienced by a person will increase a person's risk factors for suffering from other degenerative diseases, such as high blood pressure, diabetes, cancer, heart disease, and stroke.